Avian strains of emerging pathogen Escherichia fergusonii are phylogenetically diverse and harbor the greatest AMR dissemination potential among different sources: Comparative genomic evidence - Srinivas, Kandhan; Ghatak, Sandeep; Pyngrope, Daniel Aibor; Angappan, Madesh; Milton, Arockiasamy Arun Prince; Das, Samir; Lyngdoh, Vanita; Lamare, John Pynhun; Prasad, Mosuri Chendu Bharat; Sen, Arnab (Frontiers in Microbiology, 2023)
Escherichia fergusonii is regarded as emerging pathogen with a zoonotic potential. The current study focussed on a source-wise comparative genomic analyses involving resistome, virulome, mobilome and pangenome to understand the antimicrobial resistance, virulence, mobile genetic elements and phylogenetic diversity of E. fergusonii. Six E. fergusonii strains (5 multidrug resistant strains and 1 biofilm former) isolated from poultry (duck faeces and retail chicken samples) and confirmed by phenotypic and molecular methods were characterized and sequenced. Comparative resisto-virulo-mobilome analysis and pangenomics were performed for E. fergusonii genomes along with other genomes available from NCBI database. Avian and porcine strains of E. fergusonii were found to carry significantly higher number of antimicrobial resistance genes (p<0.05) and mobile genetic elements (plasmids, transposons and integrons) (p<0.05), while the pathogenic potential of bovine strains was significantly higher than other strains (p<0.05). Pan-genome development trends indicated open pan-genome for all strains (0< γ < 1). Genomic diversity of avian strains was found to be greater than that of other sources. Phylogenetic analysis revealed close clustering among isolates of similar isolation source and geographical location. Indian isolates clustered closely with Chinese isolates as well as singleton Australian isolate. Overall, being the first pangenomic study on E. fergusonii, our analysis provided important cues on genomic features of the emerging pathogen E. fergusonii while highlighting the potential role of avian strains in dissemination of AMR.